Performance Analysis of Village Apparatus in Village Government at Sugiharjo Village, District Batang Kuis, Deli Serdang Regency - Nidi Watri; Budi Hartono; Adam Adam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research is focuses on the performance of village apparatus in administering village government at Sugiharjo Village, District Batang Kuis, Deli Serdang Regency. By analysing the performance of village apparatus in accordance with the performance analysis indicators of Mangkunegara (2019) and the inhibiting factors for village apparatus performance, so that village apparatus can work optimally in carrying out their duties and support the implementation of village government and carrying out government affairs, also in community interests in accordance with the mandate of Law Number 6 of 2014 concerning Villages. This study uses a descriptive method with a qualitative approach, conducting direct interviews with Sugiharjo Village officials and the people in that village. Based on research and analysis of performance indicators: quality of work, quantity of work, discipline, initiative, and responsibility, the performance of the Sugiharjo Village Apparatus in carrying out their duties is considered not optimal, especially when there are still violations of work discipline, the violations related to working hours. Some factors inhibiting the performance of village apparatus in the form of a lack of number of village apparatus and a lack of development quality of human resources in Sugiharjo Village Apparatuses. It is necessary to make efforts to develop human resources for Sugiharjo Village Apparatuses to improve technical, theoretical and work discipline capabilities to improve apparatus performance Sugiharjo village.